A rapid and environmentally friendly analytical method based on conductive polymer as extraction phase for disposable pipette extraction for the determination of hormones and polycyclic aromatic hydrocarbons in river water samples using high-performance liquid chromatography/diode array detection. Issue 3 (June 2019) - Turazzi, Francielle Crocetta; Morés, Lucas; Carasek, Eduardo; Merib, Josias; de Oliveira Barra, Guilherme Mariz
Graphical abstract: Abstract: In this study, for the first time, an analytical methodology comprised of disposable pipette extraction technique (DPX) based on a conductive polymer (polypyrrole - PPy) was developed for the simultaneous extraction/determination of 14 compounds including two hormones and twelve polycyclic aromatic hydrocarbons in river water samples. Pipette tips of 1 mL were filled with the extraction material, named PPy.CTAB, and the separation/detection was performed HPLC-DAD. The extraction material was synthesized and characterized by Fourier transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). The optimized extraction conditions were comprised of 700 μL of sample using 2 cycles of 15 seconds each, and pH adjusted at 6.00. Regarding the desorption step, a mixture of 200 μL of acetonitrile and methanol (50:50, v/v) was used with 6 cycles of 15 seconds each. The calibration curves were performed in the sample matrix and LODs and LOQs ranged from 1.5 to 6.1 μg L -1 and from 5.0 to 20.0 μg L -1, respectively, with r ≥ 0.9901. The accuracy ranged from 44-139% and intraday precision with values ≤ 8% and interday ≤ 26%. The methodology was applied in three samples collected from Tubarão River located in the city of Orleans - SC and the analytes were not detected in these samples.